Border Studies and Political Geography: A Vision of the Hinterland and Regions of the Iberian Raya - López Trigal, Lorenzo (Geopolítica(s). Revista de estudios sobre espacio y poder, 2025)
The text aims to respond to the demand of colleagues interested in learning about the research trajectory of a Spanish scholar in the field of Border Geography, particularly in the regions and localities along the Raya (border) between Portugal and Spain. To this end, the themes and lines of research undertaken are presented, converging in a geographical study of this Iberian border: the itineraries carried out during several years of fieldwork with interdisciplinary and multinational teams, the process of Iberization of markets and the changes initiated toward an Iberian urban system, the normative frameworks and good practices of cross-border cooperation, and finally, reflections that highlight features of an emerging network of binational relations of a new kind.